The Effect of Earnings Per Share, Price to Book Value and Exchange Rate on Stock Return - Raisma Puji Pangesti; Andwiani Sinarasri; Nur Khatik (Economics and Business International Conference Proceeding, 2024)
This study aims to determine the effect of Earning Per Share, Price to Book Value and exchange rates on stock returns in food and beverage companies on the Indonesia Stock Exchange. The population in this study is all food and beverage companies listed on the Indonesia Stock Exchange, namely 30 companies, using purposive sampling techniques, obtained by 17 companies, so that the number of samples to be used is 85 observational data. The data used is secondary data, obtained through documentation. Data analysis techniques using multiple linear regression. The results of the study obtained if Earning Per Share have a positive and significant effect on stock returns, it can be seen from the calculated t value which is greater than the table t which is 2.670 > 1.990 and the significance value of 0.005 < 0.05. Proce to Book Value has a positive and significant effect on stock returns, it can be seen from the calculated t value which is greater than the table t which is 2.340 > 1.990 and the significance value of 0.010 < 0.05. The exchange rate has a negative insignificant effect on stock returns, it can be seen from the calculated t value which is greater than the table t which is -0.427 < -1.990 and the significance value of 0.671 > 0.05. The value of Fvcalculate is greater than iFitable, which is 12.776 > 2.72, and the significance value of 0.000 < 0.05, meaning that Earning Per Share, Price to Book Value, and exchange rate together (simultaneously) have a positive and significant effect on stock returns.